On economic paradigms - McCombie, John S. L. (Revista Economia & Gestão, 2008)
Is there progress in economics and, if so, how can we be certain? This may seem a strange question. After all, onehas only to compare articles in any leading economics journal today (say, the Economic Journal) with those in the samejournal fifty years ago to see a radical change. Sophisticated mathematical modelling and econometric testing using large data sets are now commonplace in modern economics articles: yet half a century ago most articles were verbaland statistical testing rudimentary.1,2 However, advances in technique should not be confused with improvements in understanding.